Demokrasi dan Komunikasi Politik Rasulullah - Azizah Fitrah (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
Prophet has succeeded in building a democratic government which is based on the Qur,an. Democracy is built on the basis of political communication that respect others, respect and uphold freedom and democratic values. Style political communication performed by the Prophet Muhammad using noble utterances, firmly straightforward, and on target. To realize a fair and dignified government.